Microneedle‐based intradermal delivery of stabilized dengue virus - Michelle E. Turvey; Divakara S.S.M. Uppu; Abdul Rahim Mohamed Sharif; Katell Bidet; Sylvie Alonso; Eng Eong Ooi; Paula T. Hammond (Wiley, 2019)
Abstract Current live‐attenuated dengue vaccines require strict cold chain storage. Methods to preserve dengue virus (DENV) viability, which enable vaccines to be transported and administered at ambient temperatures, will be decisive towards the implementation of affordable global vaccination schemes with broad immunization coverage in resource‐limited areas. We have developed a microneedle (MN)‐based vaccine platform for the stabilization and intradermal delivery of live DENV from minimally invasive skin patches. Dengue virus‐stabilized microneedle arrays (VSMN) were fabricated using saccharide‐based formulation of virus and could be stored dry at ambient temperature up to 3 weeks with maintained virus viability. Following intradermal vaccination, VSMN‐delivered DENV was shown to elicit strong neutralizing antibody responses and protection from viral challenge, comparable to that of the conventional liquid vaccine administered subcutaneously. This work supports the potential for MN‐based dengue vaccine technology and the progression towards cold chain‐independence. Dengue virus can be stabilized using saccharide‐based formulations and coated on microneedle array vaccine patches for storage in dry state with preserved viability at ambient temperature (VSMN; virus‐stabilized microneedle arrays).